The assault on reason - Gore, Albert, 1948- (New York : Penguin Press, 2007)
An analysis of how the politics of fear, secrecy, cronyism, and blind faith has created an environment dangerously hostile to reason. We live in an age when the 30-second television spot is the most powerful force shaping the electorate's thinking, and America is in the hands of an administration less interested than any previous administration in sharing the truth with the citizenry. Of even greater concern is this administration's disinterest in the process by which the truth is ascertained--an open inquiry in which unexpected and even inconvenient facts can lead to unexpected conclusions. Never has there been a worse time for us to lose the capacity to face the reality of our long-term challenges. Gore aims to make us more aware of the forces at work on our own minds, and to lead us to an understanding of what we can do to safeguard our future.--From publisher description.
The politics of fear -- Blinding the faithful -- The politics of wealth -- Convenient untruths -- The assault on the individual -- National insecurity -- The carbon crisis -- Democracy in the balance -- A well-connected citizenry -- The rebirth of democracy.
Includes bibliographical references (p. [277]-296) and index.
Keywords: Bush, George W. -- 1946-; Bush, George W. -- 1946- -- Friends and associates; Political culture -- United States; Democracy -- United States; Reason -- Social aspects -- United States; Reason -- Political aspects -- United States; Fear -- Political aspects -- United States; Official secrets -- United States; Religious fundamentalism -- Political aspects -- United States; United States -- Politics and government -- 2001-2009.